2019
DOI: 10.1016/j.adro.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The long-lasting relationship of distress on radiation oncology-specific clinical outcomes

Abstract: Purpose The diagnosis and treatment of cancer can have significant mental health ramifications. The National Comprehensive Cancer Network currently recommends using a distress screening tool to screen patients for distress and facilitate referrals to social service resources. Its association with radiation oncology–specific clinical outcomes has remained relatively unexplored. Methods and materials With institutional review board approval, National Comprehensive Cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Recent findings have shown that defense mechanisms are associated with various physical and psychological symptoms (Di Giuseppe et al, 2019a), cancer progression (Ollonen and Eskelinen, 2007), and survival probability (Beresford et al, 2006). Anxiety and depression are two psychiatric disorders commonly associated with BC (Anderson et al, 2018) and their presence is also related to higher levels of immature defense mechanisms (Hyphantis et al, 2013a; Lueboonthavatchai, 2007). However, only a few studies have used observer-rated methods and applied measures assessing the whole hierarchy of defense mechanisms (Andruccioli et al, 2009; Perry et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings have shown that defense mechanisms are associated with various physical and psychological symptoms (Di Giuseppe et al, 2019a), cancer progression (Ollonen and Eskelinen, 2007), and survival probability (Beresford et al, 2006). Anxiety and depression are two psychiatric disorders commonly associated with BC (Anderson et al, 2018) and their presence is also related to higher levels of immature defense mechanisms (Hyphantis et al, 2013a; Lueboonthavatchai, 2007). However, only a few studies have used observer-rated methods and applied measures assessing the whole hierarchy of defense mechanisms (Andruccioli et al, 2009; Perry et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…If the resolution of uncertainty is not possible, the ongoing brain-energy crisis leads to an allostatic load that contributes to systemic and brain pathology called “toxic stress” [ 57 ]. Such toxic distress, both as an acute and chronic condition, has a significant negative impact on the course and outcome of the oncological treatment [ 58 ]. That is why monitoring of the oncological patients, their psychological support and effective management of the distress are so important and highly desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these benefits, some reports have suggested that RT is also linked to higher levels of psychological distress, and patients with higher distress scores are reportedly more likely to miss appointments and to be admitted to the hospital during the RT course. 3 In addition, RT may be responsible for short-term memory loss and long-term declines in academic success due to its central nervous system toxicity. 4,5 These psychopathological comorbidities have significant impacts on patients' quality for life, self-care, and adaptation to treatment; over the course of time, they may affect cancer severity and prognosis as well as the response to treatment.…”
Section: Introductionmentioning
confidence: 99%